Skeletal muscle BOLD MRI: from underlying physiological concepts to its usefulness in clinical conditions - Jacobi, Björn (Journal of magnetic resonance imaging, 2012)
Blood oxygenation-level dependent (BOLD) MRI has gained particular attention in functional brain imaging studies, where it can be used to localize areas of brain activation with high temporal resolution. To a higher degree than in the brain, skeletal muscles show extensive but transient alterations of blood flow between resting and activation state. Thus, there has been interest in the application of the BOLD effect in studying the physiology of skeletal muscles (healthy and diseased) and its possible application to clinical practice. This review outlines the potential of skeletal muscle BOLD MRI as a diagnostic tool for the evaluation of physiological and pathological alterations in the peripheral limb perfusion, such as in peripheral arterial occlusive disease. Moreover, current knowledge is summarized regarding the complex mechanisms eliciting BOLD effect in skeletal muscle. We describe technical fundaments of the procedure that should be taken into account when performing skeletal muscle BOLD MRI, including the most often applied paradigms to provoke BOLD signal changes and key parameters of the resulting time courses. Possible confounding effects in muscle BOLD imaging studies, like age, muscle fiber type, training state, and drug effects are also reviewed in detail. J. Magn. Reson. Imaging 2012;35:1253-1265. © 2012 Wiley Periodicals, Inc.
Gesehen am 21.11.2018